Is There Really a Difference? A Comparison of In-Person and Online Qualitative Interviews - Kelly Anthony; Michelle Miller-Day; Monica Dupuy; Jarrod Ventura; Arielle Leonard Hodges; Denise Alonso-Pecora; Hannatu Dimas (International Journal of Qualitative Methods)
During the 2020 worldwide lockdowns due to COVID-19, qualitative researchers were restricted to online communication (e.g., Zoom) to gather qualitative interview data. Since that time, qualitative researchers have increasingly transitioned from conducting interviews primarily in person to conducting interviews using online communication technologies such as Zoom, but little is known about how interview approaches may impact the interview experience or data quality. This study explores differences between face-to-face (FTF) and online (Zoom) interviewing approaches, data quality, and interviewee perceptions of rapport, empathy, and conversational involvement. Participants were assigned to an interview condition (FTF or Zoom) and randomly assigned to one of two qualitative interviewers. The interview topic was mental health communication. After the interview was completed, participants completed a post-interview survey measuring perceptions of interviewer empathy, rapport, and conversational involvement. The results revealed statistically significant differences between interview conditions and participants’ perceptions of empathy and rapport. Perceptions of rapport and empathy were rated highly for both interview approaches, but significantly higher in FTF when compared to Zoom for a subset of the sample. There were no statistical differences between the FTF and Zoom approaches when considering conversational involvement or data quality.